ANTI-CD20 MONOCLONAL ANTIBODIES IN TREATMENT OF HAEMOLYTIC ANEMIA IN A TEENAGE GIRL WITH SYSTEMIC LUPUS ERYTHEMATOSUS - R. V. Denisova; E. I. Alexeeva ("Paediatrician" Publishers LLC, 2012)
Haemolytic anemia occurs in 10% of the cases of systemic lupus erythematosus in children with hematological disturbances. High doses of glucocorticoids are used for the treatment of this condition. The second-line drugs in cases of refractory disease course are azathioprine, mycophenolate mofetil, cyclosporine and cyclophosphamide. Rituximab (anti-CD20 monoclonal antibodies) is used for treatment of systemic lupus erythematosus, resistant to the standard immunosuppressive therapy. In this article a history case of successful treatment of haemolytic anemia in a teenage girl with systemic lupus erythematosus is demonstrated. Rituximab treatment allowed to avoid the increasing of glucocorticoids dose and cyclophosphamide introduction, as well as to prevent severe side-effects of afore-mentioned drugs. However in order to establish the duration of the clinical effect, safety of performed treatment and adjustment of appropriate drug dosage the data of multicenter randomized controlled trials are needed.